Childbirth in republican China delivering modernity - Johnson, Tina Phillips, 1968- (Lexington Books, 2011)
"Childbirth is a window into the shifting cultural and political landscape of a particular place and time. Much can be learned about a culture by examining its treatment of women and children. More importantly, reproduction encompasses both a moral and a social imperative; the continuation of a society rests on childbirth. In imperial China, securing the continuation of the family line was the utmost filial act, with the family as the basic organizing unit of society and the state. Yi-li Wu noted that "childbirth was the warp on which the fabric of society was woven" in imperial China. I argue that childbirth remains so, and alterations in how childbirth is viewed and conducted merely point to larger ideological visions of social and political structures. Li Xiaojiang asserted in the preface to her anthropological study of modernization and traditional childbirth customs in rural China in the 1990s that "because of its close relationship with levels of health and disease, birth is one of the keys to understanding and constructing women's lives, but our field of vision has been blind to it." Opening one's eyes to the rich material surrounding childbirth, the researcher is made aware that legislation regarding reproduction and birth, maternal and child health, and the general treatment of women and children illuminate the relative value or disregard a people carry for those women and children."--Publisher's description.